Is what’s unexpected undesirable? Investigating the expectedness and desirability of gender-stereotypic behaviors in men and women - Hannah B. Eareckson; Madeline E. Heilman (PLoS ONE, 2026)
When men and women engage in counter-stereotypic behaviors, they often face penalties for violating gender norms; however, there is evidence that men and women are not always penalized, and are sometimes even rewarded for engaging in counter-stereotypic behaviors. Existing theories of reactions to counter-stereotypic individuals make competing assumptions about the relationship between behavior gender-typicality and desirability: while theories of gender congruity assume that counter-stereotypic behaviors are inherently undesirable, expectancy violation theory assumes that desirability is largely independent of gender-typicality. In six studies, we investigate how gender-typicality affects the expectedness and desirability of twenty gender-stereotypic behaviors. Our results suggests that while behavior expectedness differs according to gender-typicality, judgments of behavior desirability are largely consistent for typical men and women (Studies 1a-1b), Black and Asian men and women (Studies 2a-2b), and successful working men and women (Studies 3a-3b). These results suggest that what is counter-stereotypic is not inherently undesirable and support the application of both expectancy violation theory and the recently proposed unified theory of gender norm violations to predict reactions to gender norm violations.